Increasing Use of Total Wrist Arthroplasty—An Australian National Joint Registry Report - Taylor, Fraser; Gilpin, Bradley David; Sivakumar, Brahman Shankar; Holder, Carl; Page, Richard; Graham, David James (Journal of Wrist Surgery, 2024)
Background and Purpose There is limited literature reporting the long-term results and outcomes of total wrist arthroplasty (TWA). The aim of this study was to describe the incidence, usage, and survival of wrist arthroplasty using data from the Australian Orthopaedic Association National Joint Replacement Registry (AOANJRR).Methods Data included all primary TWA procedures from 2006 to 2021. The primary outcome assessed was revision surgery. Utilization of TWA, etiology leading to TWA, patient demographics, and surgical factors were also assessed.Results There were 439 primary TWA procedures performed across the 16-year reporting period. Four prostheses (Motec, Universal 2, Freedom, and ReMotion) have been used, with a recent increased usage toward the Motec, which accounted for 97.4% of prostheses implanted in 2021. There has also been an increase in the number of surgeons performing TWA over time. The most common underlying etiology was osteoarthritis (72.7%), followed by rheumatoid arthritis (15.9%). Implantation for inflammatory arthropathy remained relatively constant across time; however, TWA has been utilized with increasing frequency for the treatment of osteoarthritis and other indications more recently. The cumulative percent revision at 10 years was 18.3%. Loosening accounted for 25.6% of all revisions, followed by osteolysis (12.8%), pain (12.8%), and instability (7.7%). Attempted conversion to an arthrodesis occurred in 10.3% of all revisions.Conclusion There has been an increase in both the volume of TWA performed and the number of surgeons undertaking this procedure in Australia over the past 16 years. The Motec system has become the prosthesis of choice. Medium-term revision rates are inferior when compared with Australian data for hip, knee, and shoulder arthroplasty.
Keywords: wrist; carpus; arthroplasty